An Assessment of the Accounting Techniques on Business Performance in Selected Commercial Banks in Kabale Municipality, Uganda - Moses, Agaba; Turyasingura, John Bosco (International Journal of Academic Accounting, Finance & Management Research, 2022)
Abstract: The study focused on accounting techniques for business performance of commercial banks in Kabale Municipality. The purpose of the study was to establish the relationship between accounting techniques and the performance of commercial banks in Kabale Municipality. The specific objective of the study was; To examine the accounting techniques employed by selected commercial banks in Kabale Municipality, The study adopted a cross-sectional design which was quantitative and descriptive in nature. The study sample comprised 118 respondents selected by both simple random sampling and purposive sampling. The data were tested for reliability and analysed using SPSS and results were presented based on the study objectives. Study findings revealed that the use of accounting techniques had a significant effect on the financial performance of selected commercial banks in Kabale municipality (p=.031<0.05). The study concluded that accounting techniques had a significant effect on business performance in banks. Therefore, the researcher recommended that banks should have operational accounting techniques in place which could shape the choice of financing hence resulting in better financial performance.